2017
DOI: 10.12697/eha.2017.5.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Grade nine students’ learning interests towards science topics presented in different contexts and their motivation to learn science

Abstract: a a Tartu Ülikooli loodusteadusliku hariduse keskus AnnotatsioonViimaste aastate uuringute tulemused näitavad, et õpilased hindavad üha enam loodus ainete õppimise vajalikkust, kuid endiselt on teemavaldkondi, mille õppi-mise vastu nad huvi ei tunne, kuna need on vähe seotud nende igapäevaelu või sotsiaalse keskkonnaga. Vähe on aga uuritud seda, kuidas loodusteaduslike õppeainete sisu esitamine eri kontekstis mõjutab õpilaste huvi õppekavaga kindlaks määratud teemade õppimise vastu. Artikli põhieesmärk on välj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
1
5
0
1
Order By: Relevance
“…For example, if the science themes are presented in a social and personal context (e.g., natural phenomena, effects of poisonous plants on the body), as compared with chemistry and physics-related themes, presented in an abstract format (e.g., atoms and molecules as the smallest particles of matter, electric circuits), then students' relevance is shown to be higher towards personal and social context-related themes, especially in grade 6 compared with grade 9. This result is supported by previous research which indicates that students wish to learn about the themes when they perceive them as personally relevant and also when the science content is connected with their experiences in everyday life situations, or with a social context [38,48,52]. This suggests that one way to enhance the relevance of science learning for students' in schools is by offering a variety of real-life examples in science learning, i.e., that students see the value of doing something [20].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…For example, if the science themes are presented in a social and personal context (e.g., natural phenomena, effects of poisonous plants on the body), as compared with chemistry and physics-related themes, presented in an abstract format (e.g., atoms and molecules as the smallest particles of matter, electric circuits), then students' relevance is shown to be higher towards personal and social context-related themes, especially in grade 6 compared with grade 9. This result is supported by previous research which indicates that students wish to learn about the themes when they perceive them as personally relevant and also when the science content is connected with their experiences in everyday life situations, or with a social context [38,48,52]. This suggests that one way to enhance the relevance of science learning for students' in schools is by offering a variety of real-life examples in science learning, i.e., that students see the value of doing something [20].…”
Section: Discussionsupporting
confidence: 85%
“…Value/usefulness in the SDT framework is related with the idea that people internalize and become self-regulating with respect to activities that they experience as useful or valuable for themselves [23]. Research indicates that when the science instruction is focused on usefulness and meaningfulness, students are more highly motivated and interested in learning science topics [26,[36][37][38].…”
Section: Intrinsic Motivation and Related Constructs In Terms Of Selfmentioning
confidence: 99%
See 2 more Smart Citations
“…In teacher-centred approaches, both interest and student learning are shown to be limited, whereas for student-centred approaches, where students actively participate in the learning process (e.g., inquiry-based learning, hands-on activities) these have been shown to positively promote student interest (e.g., Potvin et al, 2017;Wang et al, 2015). Furthermore, research studies have shown that student interest towards science learning is influenced by the manner in which science learning is initiated and presented to students (Hasni & Potvin, 2015;Häussler & Hoffmann, 2000;Teppo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%